Pengaruh asupan energi dan protein terhadap perubahan status gizi pasien anak selama dirawat di RSUP Dr. Kariadi Semarang - Bandawati, Bandawati; Mexitalia, Maria; Rahfiludin, M. Zen (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background : Adequate energy and  protein  intake  for  children  patients is required as efforts to prevent decline in nutritional status during hospitalization. Nutritional support is a part of therapy which has an important role in the recovery.Objective : To analyze the effect of energy and protein intake on changes of nutritional status in children patients during hospitalized.Method : Observational study with cohort prospective design, from March to April 2014. Subjects were 52 children, 2-14 years old from pediatrics unit in Dr. Kariadi Central General Hospital Semarang. Sampling were choosen by consecutive sampling, hospitalized for >7 days and according inclusion criteria. Body weight and height data were measured at admission and discharge. Nutritional status determined using weight for height Z Score, according to WHO 2005 child Growth Standards. Food intake data collected by Comstock Methode and recall 24 hours. Data analyzed by chi-square and fisher test.Result : There were 48,1% subjects with insufficient energy and 53,9% with insufficient protein intakes. 48,1% subjects  were declining in nutritional status after hospitalization. There was correlation between energy (p=0,003) and protein (p= 0,003) intakes on changes of nutritional status in children patients during hospitalized.  Subjects with insufficient energy intakes were 26 times at risk (95% CI 3,31-291,09) of declining of BW/BH Z Score than sufficient subjects. Subjects with insufficient protein intake were 20 times at risk (95% CI 4,24-230,52) of declining of weight for height Z Score than sufficient subjects.Conclusion : Insufficient energy and protein intakes can decline nutritional status in children during hospitalized.